PHOTOVOLTAIC-POWERED WATER PUMPING SYSTEM - dri, Yan (Faculty of Engineering, Universitas Tanjungpura, 2009)
Abstract Photovoltaic (PV) is a well-established, proven technology with a substantial international industry network. And photovoltaic is increasingly more cost-effective compared with either extending the electrical grid or using generators in remote locations. Water pumping is one of the simplest and most appropriate uses for photovoltaic. From crop irrigation to domestic uses, photovoltaic-powered pumping systems meet a broad range of water needs. Most of these systems have the added advantage of storing water for use when the sun is not shining, eliminating the need for batteries, enhancing simplicity and reducing overall system costs. However, the high initial investment costs are still the main obstacle to application and dissemination of these systems. The aim of this paper is to explain the basic principles of photovoltaic-powered water pumping system, including the simple design of directly coupled photovoltaic-pump system Keywords photovoltaic, water pumping, basic principles, design, main obstacle